MEMBANGUN KAPABILITAS DAN STRATEGI KEBERLANJUTANUNTUK MENINGKATKAN KEUNGGULAN BERSAING PARIWISATA BAHARI INDONESIA - Pranita, Diaz (Jurnal Vokasi Indonesia, 2016)
As the largest archipelago in the world that lies across the equator and important trade lanes of the world, the Indonesian marine tourism potential is enormous, both in terms of natural and cultural wealth. The government's commitment to build a nautical expected to contribute to the development of nautical tourism. This study proposes sustainability (sustainability) as a strategic capability that needs to be owned tourism destination to be ahead of the competition as well as how to apply the concepts of sustainability in business srategi maritime tourism destination so that sustainability can be the identity and spirit together and become a source of competitive advantage. Dimensional capabilities sustainability proposed is to prevent pollution, reduce waste and sewage, producing products responsibly, developing clean technology (clean technology), involving the local community, anticipating and advocating regulation, managing skills that are environmentally friendly, and to develop cooperation in technology development , To implement these dimensions needed leadership and a strong commitment from the organization and shared vision (shared vision).